Behind bullying and defending: Same‐sex and other‐sex relations and their associations with acceptance and rejection. Issue 6 (16th July 2013) - Veenstra, René; Verlinden, Marina; Huitsing, Gijs; Verhulst, Frank C.; Tiemeier, Henning
Abstract Relatively little is known about bullying and defending behaviors of children in early elementary school. However, this period is crucial for children's development as at this age they start to participate in a stable peer group, and difficulties in social interactions can be detected early by professionals. An interactive animated web‐based computer program was used in this study to assess peer relationships among young children. The computerized assessment was conducted among 2, 135 children in grades 1–2 from 22 elementary schools to examine the association of bullying, victimization, and defending with being accepted or rejected. Same‐sex and other‐sex peer relations were distinguished using dyadic data. Both boys and girls were more likely to accept same‐sex classmates than other‐sex classmates, and boys were more often nominated than girls as perpetrators of bullying against both boys and girls. It was found that bullies were rejected by those for whom they posed a potential threat, and that defenders were preferred by those classmates for whom they were a potential source of protection. Bullies chose victims who were rejected by significant others, but contrary to expectations, children who bullied boys scored low on peer affection. It is possible that these bullies were not strategic enough to select the "right" targets. Overall, the current findings provide evidence for strategies involved in bullying and defending at early age. Aggr. Behav. 39:462–471, 2013. © 2013 Wiley Periodicals, Inc.